Analisis Motivasi Guru Terhadap Prestasi Belajar Siswa di SD Negeri 149 Palembang - Lestari, Indah (Journal of Innovation in Teaching and Instructional Media, 2024)
The purpose of this study was to see how teacher motivation impacts student learning outcomes at SD Negeri 149 Palembang. Quantitative methods were used, using a descriptive correlational design. Data were collected through interviews and questionnaires given to 36 teachers and 204 students. The results showed a significant positive relationship between teacher motivation and student learning achievement. The novelty of this study lies in the use of empirical data to evaluate the influence of direct teacher motivation on elementary schools in Palembang. This study provides suggestions to educational policy makers on how to improve teacher motivation through training and incentive programs, so that the overall quality of education can be improved.